Distance to School is Associated with Sedentary Time in Children: Findings from the URBAN Study - Hinckson, Erica A.; McGrath, Les; Hopkins, Will; Oliver, Melody; Badland, Hannah; Mavoa, Suzanne; Witten, Karen; Kearns, Robin A. (Frontiers in Public Health, 2014)
Sedentary behavior is associated with overweight and obesity in children, and distance to school has been negatively associated with active commuting to school. It is not known how distance to school relates to sedentary behavior in children. The aim of this study was to investigate the association between distance to school and children’s sedentary behavior during weekdays at times where children interact with the neighborhood environment. Children (5-13 y, n=295) who participated in the Understanding Relationships between Activity and Neighborhoods (URBAN) study (2008-2010) across four New Zealand cities wore a hip-mounted accelerometer for seven days. Minutes spent sedentary (accelerometer count <100 min-1) were derived for the school travel periods (0800-0859 &1500-1559) and after school discretionary time (1600-1759). Shortest street network distance to school was calculated from residential addresses using Geographical Information Systems and parsed into tertiles for analysis. Children completed a daily travel log including mode of transport to and from school, which was dichotomized into active (walking and cycling) and passive (motorized) modes. Children living in the 2nd tertile of distance from school were the least sedentary during the school travelling periods (42 ± 10 %, mean ± true between-child SD) compared to those living in the 1st or 3rd distance tertiles (47 ± 10 % and 49 ± 10 % respectively); the differences were clear and likely substantial (90% confidence limits ±6%). Children who travelled by motorized transport were more sedentary for each of the distance tertiles (50 versus 44 %, 46 versus 39 %, and 54 versus 27 % for 1st, 2nd, and 3rd tertiles, respectively; 90% confidence limits ±7%). In the period of 1600-1759, girls in the 3rd distance tertile were the most sedentary. The combined effects of 1-2 km distance from school and active commuting to school contributed to least sedentary time in children.